Enhanced identification of familial hypercholesterolemia using central laboratory algorithms - Ibrahim, Shirin; Nurmohamed, Nick S.; Nierman, Melchior C.; de Goeij, Jim N.; Zuurbier, Linda; van Rooij, Jeroen; Schonck, Willemijn A.M.; de Vries, Jard; Hovingh, G. Kees; Reeskamp, Laurens F.; Stroes, Erik S.G. (Atherosclerosis, 2024)
Familial hypercholesterolemia (FH) is a highly prevalent genetic disorder resulting in markedly elevated LDL cholesterol levels and premature coronary artery disease. FH underdiagnosis and undertreatment require novel detection methods. This study evaluated the effectiveness of using an LDL cholesterol cut-off ≥99.5th percentile (sex- and age-adjusted) to identify clinical and genetic FH, and investigated underutilization of genetic testing and undertreatment in FH patients. Individuals with at least one prior LDL cholesterol level ≥99.5th percentile were selected from a laboratory database containing lipid profiles of 590,067 individuals. The study comprised three phases: biochemical validation of hypercholesterolemia, clinical identification of FH, and genetic determination of FH. Of 5614 selected subjects, 2088 underwent lipid profile reassessment, of whom 1103 completed the questionnaire (mean age 64.2 ± 12.7 years, 48% male). In these 1103 subjects, mean LDL cholesterol was 4.0 ± 1.4 mmol/l and 722 (65%) received lipid-lowering therapy. FH clinical diagnostic criteria were met by 282 (26%) individuals, of whom 85% had not received guideline-recommended genetic testing and 97% failed to attain LDL cholesterol targets. Of 459 individuals consenting to genetic validation, 13% carried an FH-causing variant, which increased to 19% in clinically diagnosed FH patients. The identification of a substantial number of previously undiagnosed and un(der)treated clinical and genetic FH patients within a central laboratory database highlights the feasibility and clinical potential of this targeted screening strategy; both in identifying new FH patients and in improving treatment in this high-risk population. [Display omitted] •FH is a highly prevalent genetic disorder increasing the risk for premature CVD, yet global diagnosis rates remain <1 %.•This study presents a novel FH detection method using existing central laboratory datasets.•1 in 4 subjects with LDL cholesterol ≥99.5th percentile had a clinical FH diagnosis and 13 % carried an FH-causing variant.•85 % of clinically diagnosed FH patients did not get recommended genetic testing, and over 97 % missed LDL cholesterol targets.•This study highlights how a laboratory-based approach can effectively identify and optimize treatment for FH patients.